Local food diversification of foxtail millet (Setaria italica) cultivars in West Sulawesi, Indonesia: A case study of diversity and local culture - Ramlah Ramlah; Marcia Bunga Pabendon; Budi Setiadi Daryono (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Daryono BS, Ramlah, Pabendon MB. 2020. Local food diversification of foxtail millet (Setaria italica) cultivars in West Sulawesi, Indonesia: A case study of diversity and local culture. Biodiversitas 21: 67-73. Foxtail millet (Setaria italica (L.) P.Beauv.) is one of the non-rice cereal crops that has long been domesticated in the world, including West Sulawesi-Indonesia as an alternative food crop instead of rice on local culture. Traditional millet cultivars may become an indispensable part of the local culture and traditions of millet-growing people across Asia over many generations. The existence of this germplasm in West Sulawesi Province, Indonesia has been observed morphologically and showed a close relationship with local culture. A total of six traditional millet cultivars (Tarreang) with different morphological characteristics have been found in this region and still preserved sustainably by the local farmers along with their local culture and traditions. The tradition of Sayyang pattu’duq may become a good example of this relationship. In this tradition, some traditional food is made by the local people like porridge tarreang, jelly tarreang, buras tarreang, jepa golla mamea, jepa anjoroi, dodol tarreang, also widely presented and used as a symbol in important ceremonies, such as celebrations in the month of Muharram, completed Al-Qur'an for children, weddings, births or show the baby's. This information may be useful as guidance for conservation and millet breeding programs in the future.